Effect of Solanum Lycopersicum on Allergic Rhinitis Symptoms: A Case Report Using Visual Analog Scale (VAS) Assessment - Dr. Krishna Raj; Dr. Tarunkumar Das; Dr. Samir Gupta; Dr. Poorav Desai (The Bioscan, 2025)
Allergic rhinitis (AR) is an inflammatory condition of the nasal lining that arises in response to environmental allergens and changes. It involves a hypersensitive reaction of the immune system, primarily triggered by an Immunoglobulin E (IgE)-mediated inflammatory mechanism. Clinically, AR is marked by four primary symptoms: sneezing, nasal discharge (Rhinorrhea), nasal itching, and congestion. It is recognized as a widespread global health issue. Homeopathic treatment focuses on stimulating the body's natural healing ability to reduce its hypersensitive response to environmental triggers, which are seen as external or exciting causes. This case study explores the therapeutic potential of Solanum lycopersicum in managing allergic rhinitis, illustrating its effectiveness in reducing symptoms and improving the patient's overall quality of life. KEYWORDS Allergic rhinitis, Homoeopathy, Solanum Lycopersicum, Vas score